Konsep Informasi dalam Perspektif Islam - Efendi, Erwan; Damayanti, Irma; Sagala, Rony Pernando; Ginting, Nadia Shaliha br (Maddah: Journal of Advanced Da'wah Management Research, 2024)
With the increasing trend of organizations adopting digital technology, the information systems within these organizations need to broaden their scope, not only for internal purposes but also to interact with the general public, government agencies, and respond to current political developments. The aim of this research is to analyze the crucial role of information systems from an Islamic perspective, to be applied by individuals in social life. The research methodology employed in this study is qualitative, utilizing valid data. The findings indicate that the application of information concepts from an Islamic perspective emphasizes the dissemination of information based on facts, honesty, and in accordance with Islamic teachings. In the context of information systems education, these concepts are highly significant and beneficial as effective means to convey information in line with Islamic teachings. The dissemination of information within this conceptual framework encompasses a wealth of knowledge for individuals to understand the essentials of information systems, the characteristics of information concepts, and the necessary components within information systems.